Incorporating technical and farmer knowledge to improve land use and management for natural flood management in lowland catchments. (May 2023) - Broadmeadow, Samantha; Nisbet, Tom; Palmer, Robert; Webb, Louise; Short, Chris; Chivers, Charlotte-Anne; Hammond, John; Lukac, Martin; Miller, Anne; Gantlett, Richard; Clark, Joanna
Abstract: Natural flood management (NFM) involves measures to restore and protect natural hydrology and geomorphology to minimise flood risk. NFM is promoted as part of the nation's flood resilience response. Government agencies have created national maps of opportunities for specific NFM measure to target available grant aid and encourage landowners and managers to deliver effective NFM measures where most needed. Mapping opportunities within a regulatory framework ensures that measures are targeted towards areas with a presumption of suitability thus minimising the burden of the application process. The viability of NFM depends on the responsible authority and community at risk accepting the proposed measures as both effective and appropriate. Top-down initiatives can fail to meet their targets when landowners and managers feel left out of the decision making and their experiential local knowledge is at odds with the spatial prioritisation derived from national datasets. This interdisciplinary paper assesses the applicability of a technical-based national mapping approach with local stakeholders for identifying opportunities for woodland and runoff management measures to reduce flood risk within the lowland catchments of the West Thames River Basin, in southern England. Farmer surveys supported the technical map in terms of targeting areas of deep clay and silt soils over mudstone as high priority for improved land and soil management to reduce rapid runoff. However, while incentives correctly target the problem areas, farmers desired greater flexibility in choice of NFM measures to reflect local soil knowledge and the sustainability of management practices within farm systems. It is argued that a more integrated and co-designed mapping approach would enhance NFM uptake and thus achieve a greater reduction in downstream flood risk. Highlights: This paper assesses the relevance of national maps to identify opportunities for NFM in lowland agricultural catchments. Farmers' experiential knowledge confirm the map correctly target areas with soils prone to degradation and surface runoff. The farmers favoured soil-based NFM measures that support continued agricultural use such as cover crops and minimal tillage. Farmers were resistant to woodland creation incentives and would prefer more support for soil and land management practices. Our study highlights the need for co-development of NFM incentives to aid delivery of national policy